TEACHERS' INDIVIDUAL PERSPECTIVE TOWARDS TEACHER PROFESSIONAL DEVELOPMENT: A NARRATIVE INQUIRY OF EFL TEACHERS IN INDONESIA CONTEXT - Fitri, Isna Anisa; Miftakh, Fauzi; Sumarta, Sumarta (IKIP Siliwangi, 2021)
In Indonesia, Participation in Teacher Professional Development activities depends on the availability of the programs and the rotation in school (Shinta Sari et al., 2020). A recent study has found some of the essential features of effective TPD are missing in Continuous Professonal Development (CPD) program. One of them was that The PKB program has not targeted teachers based on years of experience (Revina et al., 2020). Specifically, Among EFL teachers, there are only some engaging with TPD program are reported to have a positive impact on their professional lives (Cirocki & Farrell, 2019). Therefore, This qualitative research use narrative inquiry, aims to know more about the effective strategies of TPD among EFL teachers and how EFL teachers develop their TPD. The subject of the research was two EFL teacher who has been teaching English language for many years and has a lot of experience in teaching English language throughout their career. The findings from two participants indicates that for over more than 20 years of experience as an EFL teachers both participants realized how crucial Teacher Professional development to learned new knowledge and develop their professionalism from experiences throughout their entire career. By having benefits from developing extensive reading, attended some workshops and joining English community as subject focused learning related with English language teaching and the benefit of technology.Â Keywords:Â Teachers Professional Development, EFL teachers, Narrative Inquiry